Influence of water management, photoperiod and aeration on the growth, survival and early spat settlement of the hatchery-reared green mussel (Perna viridis) - Mero, Fedelia Flor Colon ([Miag-ao, Iloilo University of the Philippines Visayas, 2018)
Hatchery management strategies for the culture of pediveliger to spat in the philippine setting have not been fully developed. Hence, in an attempt to induce early spat settlement and improve mussel seed production in the country, this study aims to determine the influence of water management, photoperiod, and aeration, on the growth, survival and settlement of green mussel (P. viridis). Water in the pediveliger rearing tanks was changed every day, every 3 days and every 5 days for the water management experiemnt. Pediveligers were exposed in 24L:OD h (light : dark), 12L:12D h and OL:24D h conditions for the photoperiod experiment. Three aeration intensities were also tested - mild (10 liters-hr-1), moderate (20 liters-hr-1) and strong (30 liters-hr-1). This study demonstrated that changing water every 3 days was effective in maintainng the rearing water quality, and improving the growth and survival of P. viridis lavae. Highest growth and survival rates were observed in P. viridis spats grown in OL : 24D hours photoperiod. There was no significant difference in the settlement rate of larvae exposed to different photoperiods. Mild aeration has shown to improve the growth of P. viridis larvae but higher survival and settlement rates were attained in the strongly aerated conditions. therefore, when the larvae starts to settle, itis recommended to expose them to darkness, change the water every 3 days and provide a strong aeration to be able to attain high survival and settlement rates, and bigger spats.
Thesis (M. S. Fisheries-Aquaculture) -- [Miagao, Iloilo[ : U.P. Visayas, July 2018.